The Design and Application of the Course "Financial Statement Analysis" Under Hybrid Teaching Mode - Li, Biting (Journal of Theory and Practice of Social Science, 2024)
Hybrid teaching mode is the organic combination of online and offline teaching, so as to enrich the existing teaching resources and teaching means, and promote the flexible development of course teaching. And the financial statement analysis as train students of accounting basic theory knowledge and application ability of professional courses, teaching purpose is to promote students' understanding of the financial statements, learn to use financial statement analysis and the method of evaluation of enterprises operating results and financial condition, and so on, the traditional teaching mode cannot meet the teaching needs, Therefore, this paper aims to study the design and application of the course "Financial Statement Analysis" in the hybrid teaching mode.